Transmissão congênita em cabras reinfectadas com Toxoplasma gondii - Silva, Helenara Machado da [UNESP]; Pereira, Marina Mendonça [UNESP]; Oliveira, Thais Avila de [UNESP]; Souza, Henrique Meiroz de [UNESP]; Garcia, João Luis; Langoni, Helio [UNESP]; Richini, Virginia Bordelão [UNESP]; Bresciani, Katia Denise Saraiva [UNESP]; Soares, Vando Edésio; Costa, Alvimar José da [UNESP] (My University, 2014)
This study evaluated the potential of congenital transmission in goats experimentally infected and reinfected with Toxoplasma gondii, in three gestational stages (initial, intermediate and final). Of the 25 non-pregnant females negative for T. gondii, 20 were orally inoculated with 2.5 x 103 T. gondii ME49 oocysts. Of these, 15 pregnant females chronically infected were reinoculated, via oral, with 2.5 x 103 T. gondii VEG oocysts. Five experimental groups were formed (n=5): I, II and III (reinoculations in the initial, intermediate and final gestational stage, respectively), IV (inoculation) and V (no inoculation). Clinical and serological exams (IgG IFAT [indirect immunofluorescence antibody test]) in different days of evaluation, and bioassay and PCR were performed in all goats. In the infected goats with T. gondii a peak of 40.2°C (IV) at nine, seroconversion (IgG≥64) at 21 and stabilization (IgG<1024) at 119 days postinoculation were observed. In the reinfected goats with T. gondii occurred an increase in IgG titers (≥1,024) at 28 (I), 7 (II) and 3 (III) days post-reinoculation. During kidding were observed only in the reinfected groups: dystocia, malformation body, stillbirth and weakness, and IgG anti-Toxoplasma were detected in all and in some offsprings of the reinfected and infected goats, respectively. Tissue parasitism by T. gondii was diagnosed by bioassay and PCR in infected and reinfected goats and in their offspring. The congenital toxoplasmosis was possible in goats chronically infected and reinfected with T. gondii. The primary infection with T. gondii did not protect the pregnant goats against congenital disease resulting from toxoplasmic reinfection, in different gestational stages (initial, intermediate and final).

Avaliou-se o potencial de transmissão congênita em cabras experimentalmente reinfectadas com Toxoplasma gondii, em três estágios gestacionais (inicial, intermediário e final). Das 25 fêmeas não gestantes negativas para T. gondii, 20 foram inoculadas oralmente com 2,5x103 oocistos de T. gondii cepa ME49. Destas, 15 fêmeas gestantes cronicamente infectadas foram reinoculadas, via oral, com 2,5x103 oocistos T. gondii cepa VEG. Cinco grupos experimentais foram formados (n=5): I, II e III (reinoculações nos estágios gestacionais inicial, intermediário e final, respectivamente), IV (inoculação) e V (não inoculação). Exames clínicos e sorológicos (IgG RIFI [reação de imunofluorescência indireta]) em diferentes dias de avaliação, e bioensaio e PCR foram realizados em todos os animais. Nas cabras infectadas com T. gondii foram observados um pico de 40,2°C (IV) aos nove, soroconversão (IgG ≥64) aos 21 e estabilização (IgG <1024) aos 119 dias pós inoculação. Nas cabras reinfectadas com T. gondii ocorreu um aumento nos títulos de IgG (≥1024) aos 28 (I) , 7 (II) e 3 (III) dias pós-reinoculação. Durante o parto foram observados apenas nos grupos reinfectados: distocia, deformidades corporais, natimortalidade e fraqueza, e anticorpos IgG antiToxoplasma foram detectados em todas e em algumas crias das cabras reinfectadas e infectadas, respectivamente. Parasitismo tissular por T. gondii foi diagnosticado por bioensaio e PCR em cabras infectadas e reinfectadas e em sua prole. A toxoplasmose congênita foi possível em caprinos cronicamente infectados e reinfectados com T. gondii. A infecção primária com T. gondii não protegeu as cabras prenhes contra a doença congênita resultante de reinfecção toxoplásmica, em diferentes estágios de gestação (inicial, intermediário e final).
Congenital transmission in reinfected goats with Toxoplasma gondii
Keywords: Congenital toxoplasmosis; Goat; Toxoplasmic reinfection; VEG strain; Cabra; Cepa VEG; Reinfecção toxoplásmica; Toxoplasmose congênita